Design of Mechanical Properties of Poly(butylene-adipate-terephthalate) Reinforced with Zein-TiO2 Complex. (20th July 2022) - Togliatti, Elena; Grimaldi, Maria; Pitirollo, Olimpia; Cavazza, Antonella; Pugliese, Diego; Milanese, Daniel; Sciancalepore, Corrado
Abstract : Mechanical properties of polymer biocomposites are influenced by the interaction between the matrix and the filler surface. In this work, composites based on poly(butylene-adipate-terephthalate) (PBAT) filled with micrometric particles of zein-TiO2 complex (ZTC) were realized via solvent casting technique at different concentrations, equal to 0, 5, 10, and 20 wt%. After pelletization, the resulting materials were injection molded into standard specimens, employed for the uniaxial tensile test (UTT) characterization. From the stress-strain curves, Young's modulus (E ), yield stress (σ y ), stress at break (σ B ), elongation at break (ε B ), and toughness (T ) were collected. The addition of the ZTC proved to show a reinforcing effect on the polymeric matrix, with an increase in both E and σ y . Modelling of the mechanical properties was performed by applying Kerner's and Pukánszky's equations. Kerner's model, applied on experimental E values, returned a very good correspondence between collected and theoretical values. From the application of Pukánszky's model to σ y, the obtained B value showed a good interfacial interaction between the matrix and the filler. Due to the enhanced stiffness of the composites, a reduction in the true stress at break (σ T, B ) was observed. The modified Pukánszky's model gave a B value lower than the one obtained for the yield, but still in the range of acceptable values for microcomposites.